Stellenwert des Ultraschalls in der Urologie - Schöppler, Gita; Heinzelbecker, Julia; Michaely, Henrik J. M.; Dinter, Dietmar; Pelzer, Alexandre E. (Der Urologe, 2012)
Ultrasound is of great importance in the diagnosis of acute and chronic diseases in urology, such as kidney colic, testicular torsion, low-grade kidney trauma or for follow-up of vesicoureteral reflux, evaluation of infertility, measurement of residual urinary volume and the detection of cancer. An ultrasound examination is time and cost-effective without exposure to ionizing radiation and is routinely performed by practitioners as well as in the clinical daily routine. With technical innovations, such as contrast-enhanced ultrasound or real time elastography, it would for instance be possible to extend the application field of ultrasound. However, in some fields of investigation ultrasound still lacks accuracy and despite its many advantages the validity of ultrasound findings sometimes has to be verified with computed tomography (CT) or magnetic resonance imaging (MRI).
Gesehen am 12.07.2018
First online: 20 January 2012